Analytical theoretical approach to the transient and steady state voltammetric response of reaction mechanisms. Linear diffusion and reaction layers at micro- and submicroelectrodes of arbitrary geometry - Molina, A; González, J; Laborda, E; Compton, R (Elsevier, 2016)
A powerful theoretical approach to solve electrochemical reaction-diffusion problems with fast homogeneous kinetics is applied to obtain expressions for the transient current-potential-time response of a number of reaction mechanisms at microelectrodes of very different shapes, also applicable to ion transfer processes at liquid|liquid microinterfaces. The steady state response can be obtained as a limit when the characteristic dimension of the microelectrode tends to zero. Also, expressions under total chemical equilibrium conditions are derived when the linear reaction layer vanishes. The physico-chemical principles are based on suitable definitions of the so-called linear diffusion and reaction layers, which take into account the influence of the geometry of the diffusion field. The results presented fall within the so-called "kinetic steady state" and "diffusive-kinetic steady state" approaches and also give insight into the magnitude and extent of the perturbation of the chemical equilibrium conditions near the electrode surface as a consequence of the charge transfer process.